The influence of information technologies on the socio-economic development of territorial communities (Economics and region, 2022)
Information and communication technology development (hereinafter – ICT), which has a global trend of development, is being actively transformed into the world's global economy. The leading countries of the world began to actively use ICT in the managerial, financial and socio-economic spheres of life of the population at the macroeconomic and microeconomic levels. And in Ukraine, with the beginning of major reforms, one of the priority directions is digitization (digital transformation of society and economy). The decentralization reform, which is actively developing, requires new approaches to the formation of regional economic policy. Already at the first stages of this reform in Ukraine, they began to actively use digital technologies to work with the population. However, the place and role of Ukraine in the world rankings in ICT development is currently below average. That is why the topic is quite relevant for the scientific community because it is worth identifying the weak and strong sides of the state in the digital socio-economic sphere and identifying the most favorable ways to improve the development of Ukraine in the field of IT economy. The scientific article examines the influence of information and communication technologies on the socio-economic development of the state. Defining the role of united territorial communities in the digital economy. The directions of the digital transformation of the management system of the development of territorial communities are considered. The place and role of Ukraine in the world rankings in the rating of ICT development in the field of regional management is determined, and the first steps of the state towards the digital transformation of society and the economy.
Keywords: information and communication technologies; decentralization; reform; community; socio-economic development